The Indian Situation of Livestock Farming & Planetary Boundaries (Indian Journal of Animal Production and Management, 2024)
The crucial thing about livestock farming is that it should not affect local, regional and global human  life and environment in any way. The planetary boundaries (PB) that affect us all are – ozone  depletion, loss of biosphere integrity, chemical pollution, release of novel entities into the atmosphere,  climate change, ocean acidification, freshwater depletion, changes in global hydrological cycle, and  the land system change. Scientists note that beyond these PB, we cannot push earth systems. In  India, the situation is not yet that alarming, but steps need be initiated now to control them, as the  local/regional entities affect the global PB. For India, crucial are lowering per capita consumption and  achieving a more equitable distribution of access to resources among people. With respect to  livestock farming important aspects are land use pattern, drinking water, greenhouse gas production,  climate change and bio-physical consumption. And there are worrying aspects of costs of achieving  this. Some suggested steps needed with respect to livestock farming are – resorting to soil and eco friendly farming that puts less demands on resources; use of indigenous livestock breeds and  varieties with higher capacity to withstand harsh conditions; interventions to reduce enteric emissions  by ruminants; improved quality of dry fodders using modern technologies; better use of dung, urine  and left-over fodder; use of time-tested manure products like Panchagavya; encouraging mixed,  diversified and integrated farming systems to reduce wastes; reduce water usage by and on livestock  farms; and many-fold improvement of health care, extension, supplies and marketing to benefit small  farmers..
Keywords: Planetary boundaries; livestock farming; climate change; fresh water needs; GHG